The International Exchange Programs in the Development of the Leningrad Textile School - Shirokovskikh, Margarita S. (Actual Problems of Theory and History of Art, 2025)
The article was written with the financial support of the Russian Science Foundation, grant 23-18-00419 “Enterprises of the art industry of Leningrad in the 1940s–1960s. and their role in shaping the living environment”. The Leningrad Textile School is a phenomenon of design that unites the educational system, serial production and innovative searches of the school’s leaders — outstanding artists. The School developed actively in the early 1950s, after the restoration of the Art and Industrial school, which until 1917 was called the Central School of Technical Drawing of Baron A. Stieglitz. The Leningrad Textile School formed its own traditions, responding to the demands of the Industry and current trends in Decorative Art. This phenomenon has not been fully studied, but it is also not sufficiently understood. Based on the Study of archival materials, it was possible to find out that since the 1950s, the Leningrad Higher School of Art and Industry has been implementing international Exchange Programs with Academies and Universities in Hungary, Poland, Germany, and Great Britain. Industrial Internships were organized for the students from Leningrad at the textile factories in the Baltic countries. The article notes the contribution of the Latvian school to the development of textile art in Leningrad, carried out through cultural exchange at exhibitions and in the creative workshop Dzintari. Student internships at the Higher School of Decorative Arts in Prague in the early 1960s contributed to the development of some weaving skills, while the collaboration with the Hungarian Institute of Applied Arts influenced the development of textile design. International exchange programs existed in the Leningrad Union of Artists. Textile factories (especially the V. Slutskaya cotton-printing factory) took part in the International Industrial Exhibitions, expanding the export zone of Leningrad fabrics.